Implementation Of Marketing Strategies To Increase Sales At The Color Master Paint Shop - Suci Komala Dewi; Syahrudin, Muhammad (Journal of Business and Management Inaba, 2024)
The Index of Industrial Production (IIP) in Indonesia continues to increase, showing the progress of the industry in Indonesia. Moreover, the rapid growth of infrastructure and property will require quality paints to beautify and protect the building. The high need for attractive and diverse paint colours is one of the reasons that can be considered especially if a store only sells special editions of certain types of paint according to consumer demand. The method used is a qualitative method with Literature Review (LR). The results of this study suggest that it is necessary to implement a marketing strategy in increasing sales at the Colour Master Paint Shop. In terms of segmentation, the Colour Master Paint Shop has a positive impact, especially on geographical location. There needs to be further segment focus related to the demographic location of the Colour Master Paint Shop. As for the need to innovate product marketing with the help of E-commerce so that targeting is more widespread and sales of the Color Master Paint Shop increase